O direito constitucional ao sigilo na relação entre jornalistas e fontes de informação: contradições, conflitos e propostas - Denardi, Eveline Gonçalves (2007)
This work starts from the practical experience of the journalist, from the communication theory considering the message (the news), the transmitter (reporter) and the receptor (society) and from the use secrecy of the source in different sides of Journalism in order to analyze the central conflict of this dissertation. What is the interpretation do Journalism and Law do of the secrecy of the source? The understanding of the journalist takes into account, essentially the rigid ethics of his profession and considers it vital in all fields of Journalism. When he does not act like that, he understands that his work has been distorted. Whereas Law understands it as a constitutional (art.5º, inc.XIV) protection, but also evaluates it from the points of view of the civil law (obligation) and criminal law. The difference of perception between the journalist and the Judiciary Power regarding the secrecy of the source is that it gives origin to the conflicts in the Courts. Between journalists and their sources it is established a relationship based on trust. The commitment to the silence regarding the origin of the information is established. If the journalist breaks the confidentiality pact, he commits an act of treason which extends to consequences both in the practice of Journalism and in his professional credibility that, in turn, will harm the constitutional right to information in its three aspects: the right to inform, the right of getting informed and the right of being informed. In Brazil, even if it is possible to notice a tendency of the Judiciary Power to interpret the matter, taking into consideration the importance of the professional ethics, we verify some initiatives of those who consider themselves as victims of such constitutional protection and plead for reporters to reveal their informants in Court. One of the objectives of this work is to contribute for the best understanding of magistrates, of the journalist and society about the way news is formed. To the Judiciary Power it proposes a reading that, besides considering the juridical aspects of the theme, comprises the importance of the ethical value of that prerogative in Journalism when it ponders the judgment of demands that involve the secrecy of the source. In this way, we dedicate the first part to the study of the freedom speech in the Federal Constitution, to the right to information and the consequent conflicts between Journalism and personality rights. Next we analyze the international scenario, from similar experiences in Portugal and in the USA. Finally, we have brought in the main questions about the subject matter for the Brazilian reality